(untitled) (Oxford, 2000)
This book represents a major statement of the current research being conducted on the learning of second languages from a sociocultural perspective. The book is divided into a theoretical and an empirical part.
Keywords: Language and languages,Sociolinguistics; Study and teaching,Social aspects